Improved Photocurrents for Water Oxidation by Using Metal–Organic Framework Derived Hybrid Porous Co3O4@Carbon/BiVO4 as a Photoanode. Issue 9 (29th April 2015) - Hou, Chun‐Chao; Li, Ting‐Ting; Chen, Yong; Fu, Wen‐Fu
Abstract Efforts to improve the overall efficiency of photoelectrochemical water splitting by promoting interfacial charge transfer and suppressing electron–hole recombination remain a challenge. Highly porous Co3O4@carbon derived from metal–organic frameworks was successfully embedded on the surface of BiVO4 nanosheets. The Co3O4@carbon/BiVO4 composites were fully characterised by a variety of techniques, including powder XRD, diffuse reflectance UV/Vis spectroscopy, BET surface area calculations, SEM, TEM, energy‐dispersive X‐ray spectroscopy, high‐angle annular dark‐field scanning TEM, and X‐ray photoelectron spectroscopy. The construction of a heterojunction between porous Co3O4 (p‐Co3O4) and BiVO4 significantly promoted charge transfer and suppressed the recombination of holes and electrons. Consequently, the p‐Co3O4@carbon/BiVO4 photoanode demonstrated approximately tenfold higher photocurrent density relative to bare BiVO4 and bulk Co3O4/BiVO4 for water oxidation under the same conditions. Also, this system displayed good durability for water oxidation and could be recycled at least three times without any loss of catalytic activity.